1986
DOI: 10.1007/bf00377626
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hydrolyzable and condensed tannin on growth and development of two species of polyphagous lepidoptera: Spodoptera eridania and Callosamia promethea

Abstract: The effects of tannins on survival, growth, and digestion were compared in two polyphagous species of Lepidoptera (one, the southern armyworm, a forb-feeder; and the other, the promethea silkmoth, a tree-feeder). Two different types of tannins (hydrolyzable and condensed) were incorporated into artificial basal diets in order to determine whether or not differential survival and growth would result between the forb feeder, which normally does not encounter tannins in its natural diet, and the tree-feeder, whos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

1987
1987
2002
2002

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 33 publications
3
23
0
Order By: Relevance
“…This study, in conjunction with other studies which have failed to produce any evidence that dietary tannins reduce digestive efficiency in any insect (Betnays et al, 1980;Klocke and Chan, 1982;Reese et al, 1982;Manuwoto et al, 1985;Manuwoto and Scriber, 1986), adds further support to our contention that tannins do not deserve the status they have been accorded as general, allpurpose, digestibility-reducing substances. It is now abundantly clear that the digestive systems of insects possess a number of attributes that effectively counter the potential protein-precipitating capacity of tannins.…”
Section: Precipitation Of Rubpc From Denatured S Gregaria Gut Fluid supporting
confidence: 67%
See 2 more Smart Citations
“…This study, in conjunction with other studies which have failed to produce any evidence that dietary tannins reduce digestive efficiency in any insect (Betnays et al, 1980;Klocke and Chan, 1982;Reese et al, 1982;Manuwoto et al, 1985;Manuwoto and Scriber, 1986), adds further support to our contention that tannins do not deserve the status they have been accorded as general, allpurpose, digestibility-reducing substances. It is now abundantly clear that the digestive systems of insects possess a number of attributes that effectively counter the potential protein-precipitating capacity of tannins.…”
Section: Precipitation Of Rubpc From Denatured S Gregaria Gut Fluid supporting
confidence: 67%
“…In order to ensure that our position not be misinterpreted, we wish to emphasize that we are not proposing that tannins are innocuous chemicals that pose no problems to insect herbivores. There is no question that tannins can act as toxins (Berenbaum, 1984;Bernays et al, 1980;Manuwoto et al, 1985;Manuwoto and Scriber, 1986;Steinly and Berenbaum, 1986) and feeding deterrents (Bernays, 1981;Klocke and Chan, 1982;Reese et al, 1982;Manuwoto et al, 1985) to nonadapted insects. We are only arguing that there is no evidence that tannins reduce the nutritional value of an insect' s food by inhibiting digestive enzymes or by reducing the digestibility of ingested proteins, and further that the failure of tannins to interfere with digestion is readily explained on the basis of welldocumented characteristics of the digestive systems of herbivorous insects.…”
Section: Precipitation Of Rubpc From Denatured S Gregaria Gut Fluid mentioning
confidence: 99%
See 1 more Smart Citation
“…However, these predictions have not always held up to experimental study. Some studies have reported that tannin has no effect on certain herbivores Klocke and Chan, 1982;Manuwota and Scriber, 1986;Martin et al, 1987;Smith et al, 1992;McArthur and Sanson, 1993). One study has even suggested that tannin can be utilized by herbivores as a nutrient substrate (Bernays and Woodhead, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…However, some herbivores are well adapted to tannin-containing plants (Manuwoto and Scriber, 1986;Barbehenn and Martin, 1992). Despite numerous investigations, the precise mechanisms of tannin-herbivore interactions are still unknown.…”
Section: Introductionmentioning
confidence: 99%